PUBLIC SEARCHING OF THE WEB - AMANDA SPINK , BERNHARD J. JANSEN (Dordrecht, 2004)
The first section briefly focuses on the technology context and trends associated with Web search – the trends and growth in Web users, searches, search engines and websites. One can view the public searching of the Web from many different and often overlapping levels and contexts. This chapter discusses technological trends associated with how the public searches the Web. Figure 1.1 shows the general theoretical framework we use in the book for understanding Web search trends and issues.